CROWDSOURCING FRAMEWORK FOR MODERN ACADEMIC LIBRARY : A LITERATURE REVIEW - Syahril Ulya,; Della Kartika Sari,; Siti Aswani Mohd Ghazali,; Mohamad Rahimi Mohamad Rosman,; Norfitriah Mat Seman, (Journal of Islamic, Social, Economics and Development, 2023)
Financial problems are faced by libraries widely throughout the world, including developed or developing countries. This condition makes it difficult for libraries to adapt to modernization and reconstruction work, even to provide maximum main services. Library and Information Science (LIS) which has to be as fair as possible to ensure and sustain knowledge as a driver for development. Crowdsourcing as a new collaborative, interactive and incremental paradigm for cultural heritage and multilingual bibliographic data curation, processing and mapping for library. Crowdsourcing uses social engagement techniques to achieve a common goal by working collaboratively as a group. This is reinforced by the fact that libraries are non-profit institutions, so crowdsourcing provides more value for the money involved as well as creating a sense of shared ownership (public). The research methodology used in this paper is literature review. The data contained in the finding were collected from 2017 - 2022 from several Indonesian academic libraries' financial reports and a secondary source. The findings were that libraries faced a lack of funding for library activities and services. Academic libraries as libraries under the auspices of institutions can take advantage of crowdsourcing systems, especially in the implementation of library programs that are hindered by funding from institutions. Crowdsourcing will help academic libraries to achieve goals without funding limitations, effectiveness and time efficiency for the realization of planned programs, active community involvement, building relationships (approaches) with users and strategic marketing to attract wider and more diverse participation.